A novel multimodality endoscopic device for colonic submucosal dissection using a combination of bipolar radiofrequency and microwave modalities - Tsiamoulos, Zacharias P.; Sibbons, Paul; Morris, Steve; Hancock, Christopher P.; Saunders, Brian P. (Endoscopy, 2016)
Background and study aims: Current submucosal dissection devices are technically challenging to use, resulting in long and sometimes incomplete colonic polyp resections. The aim of this feasibility preclinical study was to evaluate a new, multimodality instrument with novel electrocautery properties. Methods: Six female adult pigs underwent colonic submucosal resections. The novel device was used to cut mucosa and submucosa using bipolar radiofrequency (BRF; at 400 KHz), provide hemostasis with microwave coagulation (MWC; at 5.8 GHz), and inject fluid via a retractable needle. The main outcomes measured were safety (histological analysis post-recovery), performance, and time needed to achieve complete resection. Results: A total of 12 consecutive colonic pseudopolyps were completely excised (two per subject) using BRF cutting. The median time to complete resection was 44.3 minutes (SD 8.9). The median defect size was 32.8 mm (SD 4.3). MWC was applied on 37 occasions for pre-coagulation or treatment of bleeding vessels. One microperforation was treated successfully with endoscopic clips. All animals recovered uneventfully during the 28-day survival period. Histology confirmed adequate healing in all postmortem defects. Conclusions: In this preclinical evaluation, the novel multimodality endoscopic device facilitated rapid and safe en bloc resection of colonic pseudopolyps.